Comparison of infection-neutralizing and -enhancing antibody balance induced by two distinct genotype strains of dengue virus type 1 or 3 DNA vaccines in mice - Fithriyah Sjatha (2018)
Dengue viruses have spread throughout tropical and subtropical countries, and vaccine development is urgently needed. However, one concern is that induction of insufficient levels of neutralizing antibodies in vaccines may increase disease severity because of a hypothetical mechanism termed antibody-dependent enhancement of infection. This study used two distinct genotype strains of dengue virus types 1 and 3 (DENV1 and DENV3, respectively) to compare antibody responses in a mouse-DNA vaccine model. As expected, a conventional neutralization test using Vero cells showed higher antibody titers in homologous rather than heterologous combinations of genotype strains used for mouse immunization and the neutralization test, for each of DENV1 and DENV3. However, our assay system using K562 cells to measure the balance of neutralizing and enhancing antibodies indicated that Vero cell-neutralizing antibody titers did not always correlate with enhancing activities observed at subneutralizing doses. Rather, induction of enhancing activities depended on the genotype strain used for mouse immunization. The genotype/strain difference also affected IgG subclass profiles and potentially the composition of antibody species induced in mice. This study suggests that enhancing activities of dengue virus-induced neutralizing antibodies may vary according to the genotype and has implications for vaccine antigen development. © 2013 Institut Pasteur.